Diode laser for excisional biopsy of peripheral ossifying fibroma - Kirti Chawla; Arundeep Kaur Lamba; Farrukh Faraz; Shruti Tandon; Abdul Ahad (Wolters Kluwer Medknow Publications, 2014)
Peripheral Ossifying Fibroma is one of the commonest occurring reactive lesions on gingiva. It is associated with local irritational factors and often interferes with speech, mastication and maintenance of oral hygiene, in addition to being aesthetically unpleasant. It is usually treated with surgical excision using scalpel and removal of irritational factors, often resulting in mucogingival defect. Other modalities such as radiosurgery and electrocautery have also been used for its management, but they cause changes in microarchitecture of biopsy specimen, altering the histologic picture for true diagnosis. We are presenting a case of excisional biopsy of this lesion in an adult female using a diode laser with excellent post-operative results, without affecting microarchitecture of biopsy specimen. The patient is being followed for last 1 year and no sign of recurrence has been found. A diode laser may offer a good alternative modality for management of such cases.